Desfechos clínicos e funcionais em pacientes hospitalizados com COVID-19 - Costa, Lara Leite (2022)
Introduction: Coronavirus disease 2019 (COVID-19) is an infection with different forms of presentation, which can culminate in acute respiratory distress syndrome, with a high potential for mortality. Survivors of the disease may experience changes such as chronic fatigue and musculoskeletal disorders after hospitalization. The Post-COVID Functional Status (PCFS) is a scale that was developed to measure the impact of the symptoms and consequences of the disease on the functional capacity of individuals. Objective: To investigate the correlation between clinical characteristics and functional outcomes in hospitalized patients with COVID19 at hospital discharge. Materials and Methods: Cross-sectional study with a quantitative approach carried out in two Brazilian hospitals. The evaluation was carried out through an interview and physical examination. The evaluators used their own form and the Fatigue Severity Scale (FSS) instruments for fatigue, EuroQoL-5D-5L for quality of life, functional status after COVID-19 with PCFS and physical capacity with the 1-minute sit-to-stand test. minute and the 1-minute arm raise test. Data were presented as absolute and relative frequency, mean ± standard deviation or median interquartile range. Results: One hundred and thirty-three (133) individuals with a confirmed diagnosis of COVID-19 were included, 56% of the sample were male. The most frequent symptoms were: dyspnea/tiredness with 51%. Regarding the functional status seen with PCFS, it was found that 27% had no functional limitations, 50% had mild functional limitations, and 23% had moderate and/or severe functional limitations. The variables that presented themselves as predictors of worse functional status in the logistic regression model were BMI (OR of 0.86 and CI95% (0.76 - 0.97)) and physical activity (OR of 2.76 and CI 95% (0 .98 - 7.80 )). Final Thoughts: Post-COVID-19 patients may have impaired physical functioning at the time of hospital discharge. In addition, the PCFS scale proved to be a useful instrument to discriminate between groups with different symptoms of fatigue, health-related quality of life, and functional performance.